Implementation Of Wadi'ah Contract As A Representative Agent For Deposit Products At BPRS Bhakti Sumekar Sumenep - Riskiyah Riskiyah; Sudianto Sudianto (International Journal of Economics, Business and Innovation Research, 2023)
Recipients of deposits that are Wadi'ah yad dhamanah in Islamic banking, can manage the deposit money. Wadi'ah yad dhamanah at BPRS Bhakti Sumekar Sumenep manages the customer's savings to be used in certain economic activities. One of the advantages that customers will receive when opening a savings accountWadi'ah yad dhamanah is to get a monthly competitive savings bonus that is given by the BPRS Bhakti Sumekar policy. Where in this case the savings product has advantages compared to other banks, so customers will benefit more if they save at BPRS Bhakti Sumekar Sumenep. The purpose of this study is to find out how the implementation of the contractWadi'ah yad dhamanah at BPRS Bhakti Sumekar Sumenep, and to find out the driving factors for contract utilizationWadi'ah yad dhamanah at BPRS Bhakti Sumekar Sumenep. The research uses descriptive qualitative research using observation, interviews, and documentation methods which are then analyzed to obtain accurate data or information. The subjects of this study were taken from several active employees at BPRS Bhakti Sumekar Sumenep, for the validity of the data the researchers used triangulation. The result of this research is the implementation of the contractWadi'ah yad dhamanah at BPRS Bhakti Sumekar Sumenep acts as a fund manager and customers as owners of capital, carries out business actions prudently and also wisely, and has good faith in carrying out financing and investments that do not conflict with sharia principles, while environmental factors and psychological factors are several factors driving the use of the contractWadi'ah yad dhamanahat Bank BPRS Bhakti Sumekar.